Desenvolvimento de ferramenta para promoção de ambientes saudáveis de trabalho em instituição hospitalar - Protótipos NATS+ - Silva, Micherlan Pereira da (2022)
Work environments add physical-structural, psychosocial, and individual and collective practices components that impact workers' experiences, their health and well-being. The study aimed to develop a tool that favors the co-participation of workers and workers' health teams in promoting healthy work environments in a hospital institution. It is methodological research for the construction of a product/tool with a participative interface, developed in a University Hospital in the City of Manaus. It was delineated in three sequential stages: (1) recognition and reasoning – between the worker's health team and workers from the internal Commission for the Prevention of Accidents; (2) construction of the tool – development of the technology according to the proposal of the subjects involved and (3) – evaluation of the tool by the target audience. In the first stage, perspectives and demands for actions to promote healthy work environments (HTA) were raised. The conceptions and contributions of workers linked to the occupational health and safety sectors report necessary conditions (material and personnel); challenges to overcome (management, recognition, wear and tear and acceptance); and suggestions for a healthier work environment, indicating components of the ATS that refertowell-beingat work, effective protection and risk control, and positive personal and professional relationships. The tool built, through the Material Designer system, was a Web Platform called “Our Healthier Work Environment (NATS +) - Tool to promote healthy work environments in hospitals”. The evaluation was carried out by the target audience participating in stage 1 and included the dimensions of the objectives, structure and presentation, relevance and adequacy of the general content and topics. Finally, as a result of the research, the NATS+ tool for promoting healthy work environments will be presented